Language, Truth, and Pedagogy - Henderson, David; Namgyal, Dadul; Risjord, Mark (Frontiers in Communication, 2021)
Early in the planning the Emory-Tibet Science Initiative, we realized that the encounter between Buddhism and contemporary science demanded that Buddhist logic and epistemology encounter Anglophone philosophy of science. A titanic clash of world views was anticipated, but as we began the conversation, we found something different. Many philosophical concerns were shared, but these problems were understood differently. While fundamental elements of epistemology, like observation and inference, had similar functions in both traditions, subtle differences in conceptualization challenged mutual intelligibility. Through thousands of years of erudite debate, each tradition had honed their tools. While each cut cleanly, they carved in different joints. This essay will briefly discuss the linguistic, philosophical, and pedagogical adjustments that made for mutual comprehensibility.